International portfolio rebalancing and fiscal policy spillovers - Sami Alpanda; Uluc Aysun; Serdar Kabaca (Bank of Canada, 2023)
We evaluate, both empirically and theoretically, the spillover effects that debt-financed fiscal policy interventions of the United States have on other economies. We first consider a two-country dynamic stochastic general equilibrium model with international portfolio rebalancing effects arising from an imperfect substitutability between short- and long-term domestic and foreign bonds. The model shows that US fiscal expansions financed by long-term debt issuance would, on net, hinder economic activity in the rest of the world (ROW). This is despite the standard trade channel's net positive effect on the ROW economy given the depreciation in the ROW currency. The fall in ROW output occurs mainly due to the increase in the ROW term premia and long-term rates through the portfolio rebalancing channel. This is because the relative demand for ROW long-term bonds decreases following the increase in the supply of US long-term bonds accompanying the fiscal expansion. Testing the predictions of our theoretical model by using panel regressions and vector autoregressions, we find empirical support for the negative relationship between ROW output and US fiscal spending. The data also confirm the positive relationship between ROW term spreads and US fiscal spending.
Keywords: E32; E62; F41; F44; 330; Economic models; Fiscal policy; International topics